P1_5 The Megapixel Limit - Boadle, Roisin Alindia; Wigfield, Emma; Dulay, Amanjit Singh (Physics Special Topics, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:EN-US; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> This article discusses the megapixel (MP) limit for a camera- the point at which the resolution of the print matches that of the eye. The limit is calculated for normal sight and for the best possible sight. It is found that for print sizes from 6x4”-18x12” the megapixel limit is 8.61-71.31MP (best sight) and 2.90-23.99MP (normal sight). The variation of the megapixel limit with viewing distance is also addressed; for an 18x12” print the megapixel limit drops below 1MP for viewing distances above 2m. Some factors affecting the visual acuity of an eye are given, and their potential effects on the MP limit mentioned.Â